Frenzied synchronicities: reworking the rhythms of temporary labour migration. Issue 2 (4th May 2021) - Perry, J. Adam
ABSTRACT: This article examines low-wage migrant workers' experiences of secondary internal mobility within Canada during the period between 2011–2016 during which the federal government imposed an immigration rule whereby migrant workers were forced to leave the country after four years of continuous residence. Introducing the concept of reworking rhythms, the article examines how a landscape of uneven and complicated immigration policies produced an environment in which low-wage temporary migrant workers in Canada had to move between subnational borders in order to find a potential pathway to permanent residence status or face compulsory repatriation within four years. The politics of a forced scheduled departure in tandem with narrow pathways to permanent residence intensified the speed with which workers had to strategize their attempts to formally convert their residence status. Drawing from interviews with workers themselves, this article examines workers' first-hand experiences of engaging in secondary internal migration to demonstrate how these frenzied attempts to synchronize the discordant rhythms of domestic life with those of international temporary labour migration were a crucial element contributing to the politics of mobility in the Canadian context.